Endoscopic Type 1 Tympanoplasty: Evaluation of Clinical Success and Hearing Improvement - Aynur ALIYEVA; Ramil HASHIMLI (Medeniyet Medical Journal)
Objective: This study aimed to assess the functional and clinical outcomes of endoscopic Type 1 tympanoplasty in patients with chronic otitis media and tympanic membrane perforations, focusing on hearing improvement and graft success rates. Methods: This retrospective study included 46 patients with dry tympanic membrane perforations who underwent endoscopic Type 1 tympanoplasty. Audiometric data, including pure tone averages (PTA) and air-bone gap (ABG) measurements at four frequencies (500, 1000, 2000, and 4000 Hz), were collected preoperatively and postoperatively. Functional success was defined as a postoperative ABG of 20 dB, whereas the integrity of the graft determined clinical success. Results: The mean preoperative ABG was 36.74+-7.62 dB, which significantly improved to 15.05+-3.82 dB postoperatively (p<0.001). The PTA exhibited an average gain of 28.17+-6.87 dB for all frequencies. Functional success was achieved in 42 patients (91.30%), with 17 patients (36.96%) achieving normal hearing and 22 patients (47.83%) presenting with slight hearing loss postoperatively. Anatomical success was achieved in 42 patients (91.30%). Conclusions: Endoscopic Type 1 tympanoplasty is a safe and effective surgical method for treating chronic otitis media, with high rates of both functional and clinical success, significant improvements in hearing outcomes, and minimal postoperative complications.